2000
DOI: 10.1111/j.1469-8749.2000.tb00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effects of botulinum toxin A: a randomized, placebo‐controlled clinical trial

Abstract: Postoperative pain in children with spastic cerebral palsy (CP) is often attributed to muscle spasm and is difficult to manage using opiates and benzodiazepines. Adductor‐release surgery to treat or prevent hip dislocation in children with spastic CP is frequently performed and is often accompanied by severe postoperative pain and spasm. A double‐blinded, randomized, placebo‐controlled clinical trial of 16 patients (mean age 4.7 years) with a mainly spastic type of CP (either diplegic or quadriplegic in distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 21 publications
1
53
0
4
Order By: Relevance
“…The study by Barwood et al 51 which found a significant reduction in post-operative pain in children with cerebral palsy secondary to a reduction in muscle spasm, has implications for the management of pain secondary to muscle spasm in other circumstances. After the use of BTX injections, the relief from pain is usually due to its effect on muscle tone rather than to any theoretical direct effect on the pain fibres.…”
Section: Other Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Barwood et al 51 which found a significant reduction in post-operative pain in children with cerebral palsy secondary to a reduction in muscle spasm, has implications for the management of pain secondary to muscle spasm in other circumstances. After the use of BTX injections, the relief from pain is usually due to its effect on muscle tone rather than to any theoretical direct effect on the pain fibres.…”
Section: Other Indicationsmentioning
confidence: 99%
“…50 Other indications for BTX-A in cerebral palsy include post-operative or post-treatment control of pain. 51 The medium-and long-term effects of the use of BTX in cerebral palsy are as yet unknown. Concerns include atrophy of muscle fibres and potentiation of muscle weakness, particularly in children with pre-existing weakness masked by spasticity.…”
Section: Cerebral Palsymentioning
confidence: 99%
“…One Class I 44 study using BoNT injection into the adductors and medial hamstrings showed an average improvement in knee-to-knee distance of about 9 cm (p Ͻ 0.002) and decrease in adductor spasticity on modified Ashworth scale of 2 (p Ͻ 0.001). Another Class I study 45 evaluated the need for postoperative pain control in children undergoing adductor muscle lengthening. There was a 74% reduction in postoperative pain (p Ͻ 0.003) and 50% less analgesic use (p Ͻ 0.005) when comparing BoNT-treated children to the placebo group.…”
Section: Spasticity Due To Cerebral Palsy In Childrenmentioning
confidence: 99%
“…We found no systematic reviews and only two randomised controlled trials and one evidence report (by the American Academy of Cerebral Palsy and Developmental Medicine). [6][7][8] …”
Section: Methodsmentioning
confidence: 99%